PENGARUH PERMAINAN PUZZLE TERHADAP BERPIKIR LOGIS PADA ANAK USIA 5 TAHUN DI TK KARTIKA 1-49 KOTA PADANGSIDIMPUAN - Iffatul Fauza; Abdul Sattar Daulay; Dina Khairiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research began with the problem of low logical thinking skills in early childhood, particularly 5-year-olds at Kartika 1-49 Kindergarten, Padangsidimpuan City. Initial observations showed that many children still had difficulty recognizing simple patterns, matching shapes, and arranging picture pieces into complete shapes. This study aimed to determine the extent to which puzzle games could influence the logical thinking skills of 5-year-olds. The method used was a quantitative approach with an experimental design, involving 36 children divided into an experimental class and a control class. Data were obtained through observation, testing, and documentation. The results of the statistical analysis showed a significant effect of puzzle games on improving children's logical thinking skills. This was evidenced by the results of the t-test, where the calculated t-value of 5.286 exceeded the t-table value of 2.120 at a significance level of 0.05. Thus, this study concluded that puzzle games significantly improved the logical thinking skills of 5-year-olds at Kartika 1-49 Kindergarten, Padangsidimpuan City.